When snails inform about geology: Pliocene emergence of islands of Vanuatu indicated by a radiation of truncatelloidean freshwater gastropods (Caenogastropoda: Tateidae). (2nd December 2013) - Zielske, Susan; Haase, Martin
Abstract The South Pacific archipelago Vanuatu has a very complex geological history including three major phases of volcanism creating island belts and phases of repeated submergence and re‐emergence. An important issue for the evolution of the biota of Vanuatu ambiguously discussed in the geological literature is the question whether the entire archipelago has been submerged until the early Pleistocene or if at least parts of the island of Espiritu Santo have remained subaerial throughout the Pliocene. We used a time‐calibrated phylogenetic analysis of freshwater gastropods of the family Tateidae based on COI, 16S rRNA and ITS2 to infer the colonization history of Vanuatu. Our analyses suggested that Espiritu Santo was colonized c. 3 Mya. Espiritu Santo was probably the place of origin for the subsequent colonization of the island of Erromango (2 Mya) and the Pleistocene radiation across the remaining archipelago. We describe 10 new species largely based on morphological and anatomical data. The genetic data in particular of the species from the young islands are taxonomically incongruent probably due to incomplete lineage sorting typical for young radiations. In contrast, the paraphyly of Fluviopupa espiritusantoana appearing in three distant clades indicates either the existence of cryptic species or the long survival of the stem species of almost the entire radiation.